IMPLEMENTASI SIRI’NA PACCE DALAM PENANGGULANGAN FRAUD - Muhammad Nur Abdi; Muhammad Adil (Universitas Muhammadiyah Sorong, 2023)
Countering fraud is important to reduce losses and respond to negative impacts. Various strategies and techniques have been developed to address fraud, such as the implementation of effective supervisory and audit systems, risk identification and fraud prevention. Therefore, handling fraud must be done proactively and continuously, taking into account new risks and developing innovative and effective solutions. The purpose of this research is to find out fraud prevention through the siri'na pacce value approach. This research uses ethnography as a method. Researchers conducted a search related to the culture of the Bugis Makassar Tribe and synthesized to find siri 'na pace in relation to fraud prevention. The 15 informants each represent government, private, academic, local youth, and general public sources. With the condition that each informant is a Bugis Macassar tribe that is closely related to the local culture of siri'na pace. The results showed that indirectly there is fraud prevention through the implementation of siri'na pacce by the Makassar Bugis community. By making self-philosophy in every decision and action so that fraud can be prevented.